Electric Field-Mediated Transport of Plasmid DNA in Tumor Interstitium In vivo - Henshaw, Joshua W. (2007)
Local pulsed electric field application is a method for improving non-viral gene delivery. Mechanisms of the improvement include electropermeabilization and electrophoresis. To understand how electrophoresis affects pDNA delivery in vivo, we quantified the magnitude of electric field-induced interstitial transport of pDNA in 4T1 and B16.F10 tumors implanted in mouse dorsal skin-fold chambers. Four different electric pulse sequences were used in this study, each consisted of 10 identical pulses that were 100 or 400 V/cm in strength and 20 or 50 ms in duration. The interval between consecutive pulses was 1 s. The largest distance of transport was obtained with the 400 V/cm and 50 ms pulse, and was 0.23 and 0.22 μm/pulse in 4T1 and B16.F10 tumors, respectively. There were no significant differences in transport distances between 4T1 and B16.F10 tumors. Results from in vivo mapping and numerical simulations revealed an approximately uniform intratumoral electric field that was predominantly in the direction of the applied field. The data in the study suggested that interstitial transport of pDNA induced by a sequence of electric pulses was ineffective for macroscopic delivery of genes in tumors. However, the induced transport was more efficient than passive diffusion.